Analisis Skema Pembiayaan Pada Ekonomi Kreatif - Ade Cahyadi Setyawan (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
This study aims to determine the financing schemes in the creative industries in Indonesia. The Government through the Creative Economy Agency has implemented various program activities to support the development of the creative economy sector, especially on access to finance. A model for facilitating access to non-banking financing with creative economy actors has also been carried out by the Creative Economy Agency. The existence of financial institutions still does not take sides with the creative economy. This is because financial institutions are constrained by the problem of the availability of physical collateral owned by creative economic actors.